PENCIPTAAN COSPLAY TOKOH WAYANG 'LIMBUK' UNTUK SENI PERTUNJUKAN URBAN DI JAKARTA - Putri Anggraeni Widyastuti; Yuke Ardhiati; Krishna Hutama (Universitas Trisakti, 2013)
AbstractIn general beginner-level cosplayer and common people think that in cosplay events, cosplayers pklay as fictional and non-fictional characters from America or Japan. However, a similar event charged this perception somewhat. In Hellofest, cosplayers not only play as characters from Japan or America, but also from Indoensia. In this event, one can find cosplayers posing as characters inspired from wayang talesOf Course, this changes the principal meaning of cosplay itself. Cosplay is the art of playacting, not unlike theatre, as in cosplay can be considered as a part of urban art. To popularize this urban event, the wayang character